2019
DOI: 10.1016/j.ijrobp.2019.02.003
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac Function After Radiation Therapy for Breast Cancer

Abstract: Take-down policy If you believe that this document breaches copyright please contact us providing details, and we will remove access to the work immediately and investigate your claim.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 40 publications
0
13
1
Order By: Relevance
“…We attribute the results of our study primarily to the successes in minimizing cardiac exposure in thoracic RT with cardiac contouring and with the increased use of DIBH techniques and some patients receiving proton therapy. Of note, the MHD in our longitudinal study was significantly lower than the previously reported series (7,9,10,26,(32)(33)(34)(35).…”
Section: Discussioncontrasting
confidence: 82%
See 1 more Smart Citation
“…We attribute the results of our study primarily to the successes in minimizing cardiac exposure in thoracic RT with cardiac contouring and with the increased use of DIBH techniques and some patients receiving proton therapy. Of note, the MHD in our longitudinal study was significantly lower than the previously reported series (7,9,10,26,(32)(33)(34)(35).…”
Section: Discussioncontrasting
confidence: 82%
“…To date, studies assessing acute radiation cardiotoxicity have had small patient numbers without the use of contemporary RT techniques and anticancer regimens (7,26). Our study design and patient enrollment more accurately reflect current chemotherapy and RT practices for breast cancer more so than previously reported in the literature (7)(8)(9)(10)26,32,33). The XXXX cohort had a high retention rate with minimal missing data (< 5%).…”
Section: Strengths and Limitationsmentioning
confidence: 94%
“…Breast cancer is the leading cause for female death, followed by colorectal cancer and lung cancer [2]. Traditional therapies for breast cancer involve surgery, radiotherapy and chemotherapy [3,4], while there are many new methods like endocrine therapy, biological target therapy and traditional Chinese medicine therapy [5,6]. Chinese medicine now has tremendous importance in chemotherapy as it has lesser side effects and toxicity [7], thus a great deal of studies has been devoted to identify novel drugs with potential for breast cancer treatment in recent years.…”
Section: Introductionmentioning
confidence: 99%
“…Notably we were able to detect this damage even earlier, as soon as 3 months following treatment with corresponding cardiac functional impairments. Other studies have demonstrated the impact of radiation dose on various segments of the heart including the left ventricle and the left mainstem coronary artery ( 25 , 26 ). Although we were unable to detect a dose—volume relationship with the observed heart damage in the basal septum, we did find that in 2 of 3 patients with heart damage over 60% of the damaged segments received a dose of 30 Gy.…”
Section: Discussionmentioning
confidence: 99%